Implikasi Yuridis Perjanjian Koalisi Politik yang Dibuat di Hadapan Notaris - Nur Kholiq (Lex Renaissance, 2017)
In 2010, Purworejo District held the Regional Head Election (Pilkada) directly. The author conducted a study of the political coalition agreement in the Purworejo District Election in 2010 by formulating the problem of how to implement the political coalition agreement and how its juridical implications. The chosen research is qualitative research that produces descriptive data. The approach chosen in this legal research is nominative-empirical, that is, regarding the implementation of normative legal provisions in action on any particular legal action during the implementation of the Purworejo District Election in 2010. From the research, the author found the role of a Notary in making political coalition agreements in District Election Purworejo. In its implementation, there are two categories of parties to the agreement. First, the agreement between the prospective regent candidates and the regent candidates who are stated in an authentic deed and made before a Notary. Second, the agreement is underhanded between the candidates for the regent and the leaders of the political party who carry it. The political coalition agreement does not have direct juridical implications for the validity of the Purworejo district election process. The agreement also cannot be used as a strong evidence for filing a lawsuit / dispute to court even though the party has found a default.Keywords: Political coalition; agreement; notary